Modulation of the photoelectrochemical behavior of Au nanocluster–TiO2 electrode by doping. Issue 24 (8th June 2020) - Naveen, Malenahalli H.; Khan, Rizwan; Abbas, Muhammad A.; Cho, Eunbyol; Lee, Geun Jun; Kim, Hahkjoon; Sim, Eunji; Bang, Jin Ho
Abstract : Optoelectronic properties of Au18 (SR)14 are modulated by Ag doping, and its influence on photoelectrochemical performance is investigated. The best compromise for light conversion efficiency is made when a single Ag atom is incorporated. Abstract : Despite the successful debut of gold nanoclusters (Au NCs) in solar cell applications, Au NCs, compared to dyes and quantum dots, have several drawbacks, such as lower extinction coefficients. Any modulation of the physical properties of NCs can have a significant influence on the delicate control of absorbance, energy levels, and charge separation, which are essential to ensure high power conversion efficiency. To this end, we systematically alter the optoelectronic structure of Au18 (SR)14 by Ag doping and explain its influence on solar cell performance. Our in-depth spectroscopic and electrochemical characterization combined with computational study reveals that the performance-dictating factors respond in different manners to the Ag doping level, and we determine that the best compromise is the incorporation of a single Ag atom into an Au NC. This new insight highlights the unique aspect of NCs—susceptibility to atomic level doping—and helps establish a new design principle for efficient NC-based solar cells.